2020
DOI: 10.15517/ijds.2020.43309
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Oral Health-Related Quality of Life in Children with Intellectual Disabilities

Abstract: Different factors can influence the perception of quality of life in individuals with intellectual disabilities. This study investigated the factors associated with quality of life related to oral health in children with intellectual disabilities from the perspective of their parents. A cross-sectional study was carried out with Brazilian children from specialized institutions and their respective guardians. Data were collected through medical records, application of instruments and oral clinical examination (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The findings of the present study showed that majority of subjects (54.3%) had poor oral hygiene and 45.7% of study participants had good oral hygiene practices. These findings are consistent with the findings of a cross-sectional study carried out among Brazilian children on factors associated with the Oral Health-Related Quality of Life in children with Intellectual Disabilities from specialized institutions which revealed that majority (64.10%) of subjects had poor oral hygiene practices [8] . The present study findings revealed that majority, 71.4% of children with intellectual disability had poor oral health and 28.6% had good oral health.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study showed that majority of subjects (54.3%) had poor oral hygiene and 45.7% of study participants had good oral hygiene practices. These findings are consistent with the findings of a cross-sectional study carried out among Brazilian children on factors associated with the Oral Health-Related Quality of Life in children with Intellectual Disabilities from specialized institutions which revealed that majority (64.10%) of subjects had poor oral hygiene practices [8] . The present study findings revealed that majority, 71.4% of children with intellectual disability had poor oral health and 28.6% had good oral health.…”
Section: Discussionsupporting
confidence: 91%
“…The dmft/DMFT was categorized according to the experience of dental caries: dmft/ DMFT 0=caries-free; 1 to 2=low experience; from 3 to 4=moderate experience and ≥5=high experience. 20 The condition of oral hygiene, assessed by the OHI-S index, is based on the amount of debris (DI-S) and dental calculations (CI-S) that affect the six representative surfaces of the teeth in the mouth. The surfaces examined for OHI-S were selected from four posterior and two anterior teeth (first right upper molar, right upper central incisor, first left upper molar, lower left central incisor, first left lower molar, and first left lower molar).…”
Section: Oral Clinical Examination and Measuresmentioning
confidence: 99%